1974
DOI: 10.1126/science.183.4131.1267
|View full text |Cite
|
Sign up to set email alerts
|

Student-Faculty Evaluation

Abstract: Desirable attributes of SFE can be vitiated by its premature utilization in a formal and quantitative sense. This is because it is possible to teach for a specific student evaluation, given a particular questionnaire. Consequently, because of the importance of SFE, the questionnaire must be designed to meet the expectations of the students, as well as the aspirations of the respective institutions. Indiscriminate use of SFE will increase the gap between first-rate and second-rate institutions-first-rate instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Some of the lowest rated items are: interesting live presentation (4*9), providing general summary at the end of the lesson (4-8), and providing outline or motivation at the beginning of the lesson. The lowest rated item, much lower than all others, is the teacher telling related anecdotes or jokes (3)(4)(5)(6). This last finding, together with the relative low ratings of live presentation shows that contrary to the belief of some teachers, entertainment does not contribute to students' appreciation of their teacher in undergraduate mathematics courses.…”
Section: (C) Students' Evaluations By Their Teachers-appropriateness mentioning
confidence: 49%
See 1 more Smart Citation
“…Some of the lowest rated items are: interesting live presentation (4*9), providing general summary at the end of the lesson (4-8), and providing outline or motivation at the beginning of the lesson. The lowest rated item, much lower than all others, is the teacher telling related anecdotes or jokes (3)(4)(5)(6). This last finding, together with the relative low ratings of live presentation shows that contrary to the belief of some teachers, entertainment does not contribute to students' appreciation of their teacher in undergraduate mathematics courses.…”
Section: (C) Students' Evaluations By Their Teachers-appropriateness mentioning
confidence: 49%
“…There is a substantive amount of research literature pertaining to undergraduate students' perceptions of good teaching [1][2][3][4][5], but it relates mainly to subject matters other than mathematics. There are no clear answers in such literature to questions such as: What do undergraduate students in mathematics regard as the main task of their teacher?…”
Section: Introductionmentioning
confidence: 99%
“…Zelby (1974) asked students to rate two courses he taught each by two different methods. Since he judged one approach to be educationally more valuable, while the students preferred the other, he concluded that "teaching for a good StudentFaculty-Evaluation may be inconsistent with the best educational practice" (p. 1269).…”
Section: Evaluation By Studentsmentioning
confidence: 99%
“…Sherman, 1976;Tetenbaum, 1975;Zelby, 1974) fear that faculty, particularly given the tight job market for academics, may teach to get good student evaluations, if such data are required and taken into account in personnel decisions. As Sherman (1976, p. 38) put it "students can be tricked into giving high ratings through highly visible changes of questionable importance."…”
Section: Evaluation To Rate Instructorsmentioning
confidence: 99%
“…High satisfaction might result because the course led to change, or because it reinforced participants' existing knowledge, attitudes, and behavior (Zelby, 1974).…”
Section: Participant Ratingsmentioning
confidence: 99%